2015
DOI: 10.9734/ijtdh/2015/19028
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Cerebrovascular Accident among North African Population (Libya) Community Based Survey

Abstract: Diabetes mellitus (DM) is a very common medical disorder and a major health problem in North Africa including Libya. DM is associated with an increase in the risk of stroke and hospitalization. Objectives: To estimate the importance of DM as a stroke risk factor among people living in Libyan community. Methodology: The study was community based descriptive cross-sectional study used CHADS2 Questionnaire, as well a local Libyan classification of stroke risk factors called Community Stroke Risk Classification (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
1
Order By: Relevance
“…According to this study, a higher incidence of diabetes in males (53.1%) compared to females (46.9%) was reported, which disagrees with a previous study from India (Ramachandran et al, 2008), and agrees with a previous Libyan study (Shambesh et al, 2015) that found that type 2 diabetes was higher in males than females (54.1% and 45.9%) respectively. This discrepancy in results could be due to an inhomogeneous study sample, which could be related to the security situation, particularly in Almarj city (Nouh et al, 2015).…”
Section: Resultscontrasting
confidence: 82%
“…According to this study, a higher incidence of diabetes in males (53.1%) compared to females (46.9%) was reported, which disagrees with a previous study from India (Ramachandran et al, 2008), and agrees with a previous Libyan study (Shambesh et al, 2015) that found that type 2 diabetes was higher in males than females (54.1% and 45.9%) respectively. This discrepancy in results could be due to an inhomogeneous study sample, which could be related to the security situation, particularly in Almarj city (Nouh et al, 2015).…”
Section: Resultscontrasting
confidence: 82%